Bibliotherapy - McNicol, Sarah; Brewster, Liz (Facet Publishing, 2018)
The basic premise of bibliotherapy is that information, guidance, wellbeing and solace can be found through reading. This book draws on the latest international practical and theoretical developments in bibliotherapy to explore how librarians, healthcare providers and arts organizations can best support the health and wellbeing of their communities. There is no standard approach to bibliotherapy. This book considers how different theories apply to different types of bibliotherapy, using case studies to illustrate how particular approaches can be used across a broad range of settings and with a variety of user groups. By focusing on the theoretical basis and history of bibliotherapy, as well as current practice, it helps to identify areas in which bibliotherapy could grow as a field of study and of practice. Bibliotherapy programmes using books to support good mental health are found around the world. The editors and their contributors present examples from public libraries, academic libraries and healthcare settings internationally - including the UK, North and South America, and Australasia. Collaboration and diversity are key themes: engaging in bibliotherapy offers librarians key opportunities to collaborate with partners outside the profession, while engaging with more diverse audiences. The book will be of interest not only to researchers and theorists, but equally to those managing bibliotherapy programmes in health, public and academic libraries. It will also be very useful for healthcare providers and those with an interest in wellbeing more generally.